(untitled) (Journal of actual problems of jurisprudence, 2018)
The article discusses features of kidnapping with other related compounds. By presupleniyam against personal freedom ottnosyatsya his abduction, false imprisonment and unlawful plmeschenie in a psychiatric hospital. Kidnapping – a “socially dangerous deliberate action aimed at removing people from their permanent residence and forcibly holding him to an unknown for relatives and law enforcement spot.” However, the place to be seen by holding all experts include the necessary features of kidnapping. Keywords: life, people, kidnapping, a crime